Costs and outcomes of treating chronic hepatitis C patients in routine care – results from a nationwide multicenter trial. Issue 2 (28th September 2015) - Stahmeyer, J. T.; Krauth, C.; Bert, F.; Pfeiffer‐Vornkahl, H.; Alshuth, U.; Hüppe, D.; Mauss, S.; Rossol, S.
Summary: Viral hepatitis is a major public health problem affecting millions of people worldwide. Long‐term consequences are the development of liver cirrhosis and hepatocellular carcinoma. The aim of the study was to assess outcomes and costs of treating patients with chronic hepatitis C in clinical practice in Germany. We carried out a prospective noninterventional study. Information on treatment outcomes, resource utilization and quality of life was provided by 281 physicians throughout Germany. Data of 3708 monoinfected HCV‐patients treated between 2008 and 2011 were analysed. Therapy consisted of peginterferon/ribavirin. Mean age of patients was 43.7 years, 60.3% were male and estimated duration of infection was 13.6 years. Predominantly genotype 1 (61.3%) or 3 (28.5%) infections were observed. Sustained viral response (SVR)‐rates in most frequently observed genotypes were 49.2% in GT‐1 and 61.9% in GT‐3 treatment‐naive patients (Relapser: GT‐1: 35.3% and GT‐3: 57.3%; Nonresponder: GT‐1: 25.0% and GT‐3: 33.3%). Average treatment costs were lowest in treatment‐naive patients (€18 965) and higher in patients who failed previous treatments (relapsers: €24 753; nonresponders: €19 511). Differences according to genotype were observed. Average costs per SVR in treatment‐naive patients were €44 744 for GT‐1 and €22 218 for GT‐3. Treatment was associated with a decrease in quality of life; post‐treatment quality of life was higher in patients achieving SVR. Our insight on real‐life treatment outcomes and costs can serve as a reference for a comparison with other treatments. There is high need for short‐term and long‐term cost‐effectiveness analysis in real‐life settings as newly introduced treatment strategies with direct acting antivirals result in high SVR‐rates but are more costly.